2013
DOI: 10.1002/chem.201302087
|View full text |Cite
|
Sign up to set email alerts
|

Paraldehyde as an Acetaldehyde Precursor in Asymmetric Michael Reactions Promoted by Site‐Isolated Incompatible Catalysts

Abstract: A song of ice and fire! The usually innocent paraldehyde can be used as an acetaldehyde precursor in an organocatalytic asymmetric Michael addition (see scheme) thanks to the proper combination of two immobilized catalysts. The site isolation induced by the polymeric supports has proven crucial to preclude deactivation of the otherwise incompatible catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…After the successful employment of vinyl acetate as an indirect source of acetaldehyde, Pericas et al 67 recently showed the use of cyclic trimer paraldehyde (110), as a precursor for acetaldehyde.…”
Section: Paraldehyde In Asymmetric Micheal Reactionmentioning
confidence: 99%
“…After the successful employment of vinyl acetate as an indirect source of acetaldehyde, Pericas et al 67 recently showed the use of cyclic trimer paraldehyde (110), as a precursor for acetaldehyde.…”
Section: Paraldehyde In Asymmetric Micheal Reactionmentioning
confidence: 99%
“…In order to overcome the problems of low boiling point and high reactivity of acetaldehyde, several groups attempted the use of acetaldehyde surrogates, such as paraldehyde and vinyl acetate, in asymmetric organocatalytic cross‐aldol reactions. In particular, vinyl acetate is typically used as an acyl donor in enzyme‐catalyzed transesterification reactions.…”
Section: Enantioselective Reactions Using Simple Acetaldehydementioning
confidence: 99%
“…Similarly to the aldol reaction, three molecules of acetaldehyde are generated by the reaction of paraldehyde with polymer‐bounded p ‐toluenesulfonic acid ( 12 ) which then undergo Michael addition with β‐nitroolefin through enamine catalysis. The best result (91 % ee ) was obtained when the two incompatible solid‐supported (co)‐catalysts were confined into a teabag, in CH 2 Cl 2 (Scheme ) …”
Section: Enantioselective Reactions Using Simple Acetaldehydementioning
confidence: 99%
“…In our approach, [11] cheap and easy-to-handle paraldehyde (3.7 € per mol; b.p. 123 O C) is employed as a convenient source of acetaldehyde, which is slowly generated by acid-catalyzed deoligomerization (polystyrene-bound sulfonic acid).…”
mentioning
confidence: 99%
“…Noteworthy, the combined use of 1 b/2 under these conditions does not require the physical separation of the two resins, as was the case for the combined use of the silyl ether of 1 a and 2 in Michael additions of acetaldehyde. [11] The scope of the cross-aldol reaction was studied next under the optimized reaction conditions, and the results are listed in Table 2. It was established that benzaldehydes with either ortho, meta, or para electron-withdrawing substituents afforded the desired cross-aldol products with generally good yields and excellent enantioselectivities ( Table 2, entries 1-9).…”
mentioning
confidence: 99%